Management of hyperthyroidism in pregnancy - Aggarwal, Rashmi; Chugh, Pradeep (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Hyperthyroidism in pregnancy is associated with adverse foetal, maternal and obstetrical outcome. Untreated or inadequately treated hyperthyroidism may precipitate pre eclampsia and congestive cardiac failure in mother. It also increases the risk of miscarriage, abruption placentae and premature delivery in such patients. Maintaining euthyroidism in these patients is of utmost importance. Antithyroid medications are used as first line treatment for such patients to restore euthyroid status at the earliest. Radioactive iodine is absolutely contraindicated in pregnancy and surgery often requires pre-treatment with anti thyroid medications. Two drugs are available –carbimazole and propylthiouracil. Use of carbimazole/methimazole in pregnancy is not only associated with increased incidence of scalp defect(aplasia cutis ) in the infants, but some specific congenital malformation like choanal atresia, oesophageal atresia, trachea-oesophageal fistula, patent vitello intestinal duct, omphalocele, dysmorphic facial features and growth retardation do occur. These malformations represent carbimazole /methimazole embryopathy. Due to the association of foetal teratogenicity with carbimazole /methimazole, propylthiouracil is recommended as the drug of choice in first trimester of pregnancy. However, as its use is associated with risk of hepatotoxicity, it should be changed to carbimazole/methimazole thereafter.